1986
DOI: 10.1021/bi00371a035
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting surface expression of glycolipids: influence of lipid environment and ceramide composition on antibody recognition of cerebroside sulfate in liposomes

Abstract: The reactivity of the acidic glycolipid cerebroside sulfate (CBS) with antibody was studied as a function of its lipid environment in vesicles and of its ceramide composition. The lipid environment was varied by using phosphatidylcholine of varying chain length with cholesterol in a phosphatidylcholine:cholesterol:cerebroside sulfate molar ratio to glycolipid of 1:0.75:0.1. The ceramide structure of CBS was varied by using synthetic forms containing palmitic acid, lignoceric acid, or the corresponding alpha-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 35 publications
4
45
0
Order By: Relevance
“…These authors found that the shorter the fatty acyl chain in these glycosphingolipids, the stronger their immunomodulatory effect. In contrast, lipid structural variations seem not to be involved in antigenic recognition of DAT (44), as is the case for some glycosphingolipids (10,32).…”
Section: Discussionmentioning
confidence: 99%
“…These authors found that the shorter the fatty acyl chain in these glycosphingolipids, the stronger their immunomodulatory effect. In contrast, lipid structural variations seem not to be involved in antigenic recognition of DAT (44), as is the case for some glycosphingolipids (10,32).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, X-ray crystallography of galactosylceramide with sphingosine and 2-hydroxystearic acid demonstrated a shovel-like overall shape [24], whereas an NMR study of glucosylceramide with sphingosine and palmitic acid proposed a straighter conformation [25]. Furthermore, studies with anti-glycolipid antibodies and binding to intact cells [26] or well-defined liposomes [27] support the idea that the ceramide structure may direct the sugar head group conformation.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of cell membrane receptor GSL 2 carbohydrate for protein ligand binding is influenced by both the nature of the GSL lipid moiety and the membrane microenvironment (1), from early reports of membrane GSL "crypticity" (2-4) and lipid dependent anti-GSL binding (5)(6)(7), to recent fatty acid-dependent GSL bilayer remodeling (8,9). The plane of the membrane bilayer, in relation to membrane GSLs, can markedly affect the conformation of the carbohydrate (10) to promote the availability of different epitopes within the same GSL sugar sequence (11).…”
mentioning
confidence: 99%